Slope Stability Analysis and Stabilization : New Methods and Insight - Cheng, Y. M. and Lau, C. K. (Boca Raton : CRC Press, 2014)
This book provides a critical review of these and offers several more appropriate approaches for overcoming numerical convergence and the location of critical failure surfaces in two-dimensional and three-dimensional cases. New concepts in three-dimensional stability analysis, finite element analysis and the extension of slope stability problems to lateral earth pressure problems are also addressed. It gives helpful practical advice and design resources in the form of recommendations for good analysis and design practice, design charts and tables for the engineer. --
1. Introduction -- 2. Basic slope stability analysis methods -- 3. Location of critical failure surface, convergence and advanced formulations -- 4. Finite-element methods for slope stability analysis and comparisons with limit equilibrium analysis -- 5. Three-dimensional slope stability analysis -- 6. Implementation -- 7. Routine assessment of feature and design of landslip preventive measures -- 8. Numerical implementation of slope stability analysis methods.
A Spon book.
Includes bibliographical references and index.
Also available in print format.
Keywords: Slopes (Soil mechanics); Soil stabilization; Electronic books